Zainuddin Al-Malibari's Fiqh of Diversity in Fatḥ Al-Mu’īn - Sholihuddin, Muh; Jazil, Saiful; Zahro, Ahmad; Niam, Syamsun; Nurhayati, Anin (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This research elucidates the thoughts on the fiqh of diversity by Zainuddin al-Malibari in the book Fatḥ al-Mu’īn, aiming to conceptually elaborate on Zainuddin al-Malibari's views on the fiqh of diversity and its relevance in fostering harmony in diversity in Indonesia. This research employs a historical approach through library research data. Data analysis involves both content analysis and comparative analysis. The fiqh of diversity elaborated through the concept of jihād by Zainuddin al-Malibari, understood broadly, not just as warfare but also as preaching, can serve as a fundamental value for fostering community harmony in Indonesia. It is essential in maintaining harmony among a society of different ethnicities, religions, and groups. Zainuddin al-Malibari's fiqh of diversity in the book Fatḥ al-Mu'īn emphasizes the importance of realizing the maqāṣid al-sharī'ah principle. Which aims to achieve essential benefits, namely the preservation of religious freedom (ḥifz al-dīn), the protection of every individual's life (ḥifz al-nafs), the safeguarding of the community's economic access (ḥifz al-māl), equal access to education for all members of society (ḥifz al-‘aql), and the protection of the rights of every family (ḥifz al-nasl).